Stereoselective functionalization of platensimycin and platencin by sulfa-Michael/aldol reactions. Issue 17 (28th February 2019) - Qiu, Lin; Wen, Zhongqing; Li, Yuling; Tian, Kai; Deng, Youchao; Shen, Ben; Duan, Yanwen; Huang, Yong
Abstract : Bioinspired cascade reactions involving sulfa-Michael/aldol reactions have been developed for the step-economical construction of thia-ring analogues of platensimycin and platencin. Abstract : Bioinspired sulfa-Michael/aldol cascade reactions have been developed for the semisynthesis of sulfur-containing heterocyclic derivatives of platensimycin and platencin, with three newly formed contiguous stereogenic centers. Density functional theory calculations revealed the mechanism for the stereochemistry control. This method was used in a synthesis of a platensimycin thiophene analogue with potent antibacterial activities against Staphylococcus aureus .